Does self-efficacy influence recovery and well-being in osteoarthritis patients undergoing joint replacement? A systematic review. (September 2014) - Magklara, Eleni; Burton, Christopher R; Morrison, Val
Objective: To investigate the role of self-efficacy in functional recovery and well-being outcomes in osteoarthritis patients, undergoing hip or knee replacement surgery. Data sources: Studies were identified using MEDLINE via PUB med, PsycINFO and CINAHL from inception to July 2013. Methods: Three search strategies that combined key terms of 'self-efficacy', 'functional recovery', 'well-being' and 'joint replacement' were applied. Titles and abstracts were screened for eligibility and, accordingly, potentially eligible studies were retrieved for review. Included studies were assessed in terms of their quality, and data were extracted by two independent reviewers. A narrative synthesis of results was conducted. Results: In total, 836 articles were identified and after electronic de-duplication, 708 articles remained. After screening 15 articles were retrieved as potentially eligible and eight articles were included in the review. Of the eight studies ( n = 967 patients), seven had a prospective design and all studies were considered of good quality. No fully conclusive evidence for the influence of self-efficacy upon functional recovery outcomes was found. When the timing of self-efficacy measurement was examined, post-operative self-efficacy was found to be related to functional recovery outcomes. Conclusion: Presurgical self-efficacy was the least consistent predictor of functional outcomes while postoperative self-efficacy was more consistently associated with recovery outcomes such as longer distance ambulation, exercise repetition and frequency, walking speed and disability.